Peningkatan Kemampuan Guru Dalam Menyusun Rpp Satu Lembar Dengan Metode Focus Group Discusion Di Sd Negeri 3 Sumberagung Kecamatan Klego Kabupaten Boyolali Tahun Pelajaran 2019/2020 - Endang Kartini (Publikasi Indonesia, 2022)
This research is School Action Research (PTS). The subjects of the study were teachers of SD Negeri 3 Sumberagung, Klego District, totaling 8 people. Data collection techniques are: coesioner, observation, assignment, and documentation. Data validity using source and method trianggulation. Data analysis using interactive model analysis and descriptive statistics The results of the study concluded: (1) Through the Small Group Discussion method, it is able to increase the active participation of discussion participants (teachers) to exchange experiences and thoughts in solving problems related to the preparation of a one-sheet rpp; (2) Through the Small Group Discussion method, it is able to create a pleasant and conducive training or guidance atmosphere to transfer knowledge, because each discussion participant (teacher) can give and receive each other's understanding discussed; (3) Through the Small Group Discussion method, it is effective to improve the ability of discussion participants (teachers) in preparing a one-sheet learning implementation plan (RPP).